2003
DOI: 10.1189/jlb.1202628
|View full text |Cite
|
Sign up to set email alerts
|

High expression of p21Waf1 in sarcoid granulomas: a putative role for long-lasting inflammation

Abstract: In sarcoid granulomas, apoptotic events are reduced, which explains their characteristic long-lasting inflammation. We have described that interferon-gamma (IFN-gamma) inhibits apoptosis in macrophages through the expression of p21(Waf1). Here, we explore the molecular mechanisms involved in the inhibition of apoptosis in sarcoid granulomas. We analyzed skin biopsies from 19 sarcoidosis patients and 16 controls. Total RNA was subjected to semiquantitative reverse transcriptase-polymerase chain reaction analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 38 publications
(52 reference statements)
0
11
0
Order By: Relevance
“…DAP, an ubiquitin homology protein, has been shown to suppress NF-kB/Rel activity, to interact with the death domain of TNF-R1 (Tumor necrosis factor receptor 1) and to trigger program cell death in a variety of cell lines (Liou and Liou 1999;Raveh et al 2000). The potential relevance is that a balance between apoptosis and inXammatory cell survival provides a fundamental mechanism for immune system homeostasis and one proposed mechanism for the chronic granulomatous inXammation in sarcoidosis is through altered apoptosis (Mermigkis et al 2005;Xaus et al 2003;Stridh et al 2002). Granzymes A and K (GZM A and K), located on chromosome 5q11-12 approximately 1.5 cM from D5S407, are serine proteases released from the granules of cytotoxic lymphocytes which induce apoptosis and are expressed in PBMCs (Bade et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…DAP, an ubiquitin homology protein, has been shown to suppress NF-kB/Rel activity, to interact with the death domain of TNF-R1 (Tumor necrosis factor receptor 1) and to trigger program cell death in a variety of cell lines (Liou and Liou 1999;Raveh et al 2000). The potential relevance is that a balance between apoptosis and inXammatory cell survival provides a fundamental mechanism for immune system homeostasis and one proposed mechanism for the chronic granulomatous inXammation in sarcoidosis is through altered apoptosis (Mermigkis et al 2005;Xaus et al 2003;Stridh et al 2002). Granzymes A and K (GZM A and K), located on chromosome 5q11-12 approximately 1.5 cM from D5S407, are serine proteases released from the granules of cytotoxic lymphocytes which induce apoptosis and are expressed in PBMCs (Bade et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, several particular target genes of the “Pathways in Cancer” have been indeed indicated in wet laboratory to be dysregulated at their protein and/or mRNA level in sarcoidosis [3136]. Among them, WNT (wingless and integrase-1)7A, catenin-beta, and transforming growth factor- (TGF-) β are concurrently involved into other signalling pathways, including the WNT and TGF- β signalling pathways [23].…”
Section: Discussionmentioning
confidence: 99%
“…AIM deficiency resulted in apoptosis of granuloma infiltrating T and NK T cells. Some have suggested that induction of p21 WAF by IFN-␥ could be a mechanism for the low apoptotic activity observed in sarcoid granulomas [52]. In addition to these specialized apoptotic signaling pathways, stimulation through the T cell receptor is known to affect T cell survival and proliferation, but this has not been directly studied within granulomas.…”
Section: Survival and Proliferation In The Granulomamentioning
confidence: 99%